An evaluation of peptone as a specialty protein source in diets for nursery pigs - C K Jones; D McKilligan; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
Two experiments were conducted to evaluate the effects of select menhaden fish meal (SMFM), spray-dried animal plasma (SDAP), and two forms of a spray-dried ultra-filtrated porcine intestinal mucosa (Peptone 1 and 2; Protein Resources, West Bend, IA) on nursery pig performance. In Exp. 1, 216 weanling pigs (initial BW 11.9 lb) were fed either (1) a control diet containing no specialty protein sources or the control diet with (2) 4% SMFM during Phase 1 and 2% SMFM during Phase 2, (3) 4% SDAP during Phase 1 and no specialty protein sources during Phase 2, (4) 4% SDAP during Phase 1 and 2% SDAP during Phase 2, (5) 4% Peptone 1 during Phase 1 and no specialty protein sources during Phase 2, or (6) 4% Peptone 1 during Phase 1 and 2% Peptone 1 during Phase 2. Pigs were fed Phase 1 diets from d 0 to 10 postweaning followed by Phase 2 diets from d 10 to d 20 and a common Phase 3 diet that contained no specialty proteins for 7 d. From d 0 to 10 or d 0 to 27, there were no differences (P>0.05) in ADG or F/G. In Exp. 2, 180 weanling pigs (initial BW 13.0 lb) were fed either (1) a control diet containing no specialty protein sources or the control diet with (2) 4% SMFM during Phase 1 and 2% SMFM during Phase 2, (3) 4% SDAP during Phase 1 and no specialty protein sources during Phase 2, (3) 4% SDAP during Phase 1 and 2% SDAP during Phase 2, (5) 4% Peptone 2 during Phase 1 and no specialty protein sources during Phase 2, or (6) 4% Peptone 2 during Phase 1 and 2% Peptone during Phase 2. Pigs were fed Phase 1 diets from d 0 to 10 postweaning followed by a Phase 2 diet from d 10 to d 25. Pigs were then fed a common Phase 3 diet that contained no specialty proteins for 7 d. From d 0 to 10, pigs fed diets containing Peptone 2 had improved (P<0.10) F/G compared with pigs fed the control diet. Overall (d 0 to 32), pigs fed 4% Peptone 2 during Phase 1 and 2% Peptone 2 during Phase 2 had improved (P<0.05) ADG compared with pigs fed 4% SMFM during Phase 1 and 2% SMFM during Phase 2. Pigs fed 4% Peptone 2 during Phase 1 and 2% Peptone 2 during Phase 2 had improved (P<0.05) F/G compared with pigs fed all other diets. In conclusion, the Peptone products evaluated in these studies can be used in nursery pig diets without negatively affecting pig growth performance. However, the lack of response to animal plasma in these experiments indicates that further research is warranted.; Swine Day, Manhattan, KS, November 19, 2009
Keywords: Swine day; 2009; Kansas Agricultural Experiment Station contribution; no. 10-014-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1020; Growth; Protein source; Spray-dried intestinal mucosa; Swine